Advanced Raman spectroscopy of Cs2AgBiBr6 double perovskites and identification of Cs3Bi2Br9 secondary phases. (15th July 2020) - Pistor, Paul; Meyns, Michaela; Guc, Maxim; Wang, Hai-Chen; Marques, Miguel A.L.; Alcobé, Xavier; Cabot, Andreu; Izquierdo-Roca, Victor
Abstract: Cs2 AgBiBr6 double perovskites are intensely investigated as lead-free, stable alternatives to organic lead halide perovskites. In this contribution, we revise the vibrational modes of Cs2 AgBiBr6 and show that Raman spectroscopy is well suited for the detection of common secondary phases such as Cs3 Bi2 Br9 . The combined Raman analysis at pre-, near- and non-resonant conditions allows us to extract the four vibrational modes of Cs2 AgBiBr6 to unprecedented detail, the most intense one at 177.3 cm -1 . The experimental results are in good agreement with theoretical density functional theory calculations. In addition, we monitor the decomposition of Cs2 AgBiBr6 into Cs3 Bi2 Br9 at temperatures above 255 °C. Graphical abstract: Image, graphical abstract